The PR/SET domain zinc finger protein Prdm4 regulates gene expression in embryonic stem cells but plays a nonessential role in the developing mouse embryo. - Bogani, D; Morgan, M; Nelson, A; Costello, I; McGouran, J; Kessler, B; Robertson, E; Bikoff, E (2013)
Prdm4 is a highly conserved member of the Prdm family of PR/SET domain zinc finger proteins. Many well-studied Prdm family members play critical roles in development and display striking loss-of-function phenotypes. Prdm4 functional contributions have yet to be characterized. Here, we describe its widespread expression in the early embryo and adult tissues. We demonstrate that DNA binding is exclusively mediated by the Prdm4 zinc finger domain, and we characterize its tripartite consensus sequence via SELEX (systematic evolution of ligands by exponential enrichment) and ChIP-seq (chromatin immunoprecipitation-sequencing) experiments. In embryonic stem cells (ESCs), Prdm4 regulates key pluripotency and differentiation pathways. Two independent strategies, namely, targeted deletion of the zinc finger domain and generation of a EUCOMM LacZ reporter allele, resulted in functional null alleles. However, homozygous mutant embryos develop normally and adults are healthy and fertile. Collectively, these results strongly suggest that Prdm4 functions redundantly with other transcriptional partners to cooperatively regulate gene expression in the embryo and adult animal.